STRATEGI PENINGKATAN PRODUKTIVITAS KOMODITI BAWANG MERAH MELALUI INOVASI PUPUK HAYATI MIKORIZA DI KABUPATEN PIDIE - Safrida Safrida; Ismail Sulaiman; Syafruddin Syafruddin; Syamsudin Syamsudin; Hasanuddin Hasanuddin; Hadianur Hadianur (Universitas Teuku Umar, 2022)
Pidie Regency is one area that has the potential to become a centre for onion production. This area also has the potential to fill the supply of onions in big cities in Aceh Province, thereby reducing dependence on supplies from Java, especially Brebes, and North Sumatra or West Sumatra. To support the government's program, namely shallot self-sufficiency in 2021, the development of shallot commodities is carried out by increasing the productivity of onions by using the biofertilizer MIKORIZA. It is hoped that with the application of mikoriza biofertilizer innovation, the farmers' onion yields can produce optimal onion production, and can achieve the national average productivity. This activity was carried out in 2 sub-districts in Pidie District, namely: Keumala District and Tangse District. Each sub-district was selected by one farmer group. This service activity is carried out using counselling and guidance methods on the application of mikoriza on onion plants. The results of the service showed that there was an increase in the production of onions in the two sub-districts up to 12.5 percent from the results of previous onion plantings without the use of mikoriza